AKUNTANSI SEBAGAI REALITAS EKONOMI DAN KEAGAMAAN: MENGUNGKAP NILAI-NILAI RELIGIUS MELALUI FOTO DALAM LAPORAN TAHUNAN PERBANKAN SYARI’AH - Pratiwi, Rahasanica Nariswari; Chariri, Anis (Diponegoro Journal of Accounting, 2015)
The role of accounting in Sharia Banking is not only as economic reality but also as religious reality. Religious reality constructed by religious value in annual report of Sharia Bank. Thus, the purpose of this paper is to understand and analyze the existence of religious values by form of photographs in annual report, and to analyze thereas on of religious values disclosure in annual report. Ontologically, this study is build on a belief that annual report is a communication media to show the ways Sharia Banks express adherence to sharia principle.The research has done by analyzing the photographs in annual report of Bank Muamalat Indonesia (BMI), Bank Syariah Mandiri (BSM), Bank Rakyat Indonesia (BRI), Bank Central Asia (BCA) Syariah, and Bank Negara Indonesia (BNI) Syariah in Indonesia. This study is qualitative research, was carried out with in interpretive paradigm using semiotic approach.The results of this study also show that photographs in annual report of Sharia Banks in this research contained religious values. Furthermore, this study concludes that Sharia Banks actually expressed religious reality and make them different from the other bank’s annual report which focuses only on economic reality. This indicates Islamic Banks obedience existence about responsibility, not only to the stake holders but also to the society and Allah.